PENGARUH HAMBATAN SAMPING TERHADAP KECEPATAN DAN ARUS LALULINTAS - Irfan Irfan (Universitas Teuku Umar, 2017)
Meulaboh Busines area on Jalan H. Daut Dariah II is a busy area with trade activities, especially during rush hour. Parking activities around the Meulaboh market especially on Jalan H. Daud Dariah I is so high that the shoulders and road bodies are filled with parking cars, motorcycles, tricycles, and street vendors. In addition, the pedestrians cross the road and the number of motor vehicles coming in and out of the center of the market as well as the slow moving vehicles like bicycles, tricycles and carts. This causes the road width to be less effective so that the speed of traffic becomes low and there is traffic congestion. The purpose of this study is to analyze the effect of side barriers on the speed and flow of lalulitas and the factors that predominantly influence side obstacles are in and out vehicles, parking vehicles and street vendors. Side obstacle data, speed and traffic volume was taken directly by conducting survey for 7 days and analyzed by using Manual of Capacity of Road Indonesia 1997. From result of calculation hence side barrier influence highest happened at period time clock 09.00 - 10.00 this is caused by the number of vehicle The parking and the vehicles going in and out, at this condition the speed of the vehicle decreased to 20.62 km / h for two-wheeled vehicles or tricycles and for the speed of four-wheeled vehicles of 15.82 km / h with traffic flow of 274.64 smp / hour. To increase the speed and traffic flow on the road H. Daud Dariah I then need to be provided in the parking lot so that vehicles are no longer parked on the road and pedangang pedestrians should sell at places that have been provided by the government. Keywords : obstracle, speed, traffic flow